Moderasi Beragama Dalam Menciptakan Nilai-Nilai Toleransi Dan Kerukunan - Aisyah; Aisyah Hayatun Suaibah; Muhammad Kamil (4, 2024)
In the era of globalization of the 21st century, harmony and peace between religious communities is becoming increasingly important. The concept of religious moderation has emerged as a promising solution for creating tolerance and harmony amidst diversity. This article aims to examine the concept of religious moderation and its implementation in building a tolerant and harmonious society. Through literature studies, this research identifies key elements of religious moderation, such as an open attitude, mutual respect, and commitment to universal human values. Furthermore, it also discusses how religious moderation can be applied in everyday life, both within the family, community and wider society. This research concludes that religious moderation is an effective approach in maintaining social harmony and creating a tolerant and harmonious society. In the Indonesian context which is rich in religious, cultural and ethnic diversity, religious moderation is important in maintaining tolerance and harmony between religious communities. Further efforts are needed to apply this concept to everyday life and overcome the persistent challenges of religious-based intolerance and conflict. Abstrak Dalam era globalisasi abad ke-21, keharmonisan dan kedamaian antar umat beragama menjadi semakin penting. Konsep moderasi beragama muncul sebagai solusi yang menjanjikan untuk menciptakan toleransi dan kerukunan di tengah keragaman. Artikel ini bertujuan untuk mengkaji konsep moderasi beragama dan implementasinya dalam membangun masyarakat yang toleran dan rukun. Melalui studi literatur, penelitian ini mengidentifikasi elemen-elemen kunci moderasi beragama, seperti sikap terbuka, saling menghargai, dan komitmen terhadap nilai-nilai universal kemanusiaan. Selanjutnya, dibahas pula bagaimana moderasi beragama dapat diterapkan dalam kehidupan sehari-hari, baik di lingkungan keluarga, komunitas, maupun masyarakat luas. Penelitian ini menyimpulkan bahwa moderasi beragama merupakan pendekatan efektif dalam menjaga keharmonisan sosial dan menciptakan masyarakat yang toleran serta rukun. Dalam konteks Indonesia yang kaya akan keragaman agama, budaya, dan etnis, moderasi beragama menjadi penting dalam menjaga toleransi dan kerukunan antarumat beragama. Upaya yang lebih lanjut diperlukan untuk menerapkan konsep ini dalam kehidupan sehari-hari dan mengatasi tantangan intoleransi dan konflik berbasis agama yang masih ada.